Thinking Safety: Making the Familiar Strange and the Strange Familiar: Body/Space Investigations of Womens Safety in Cape Town - Ajak, Abul Oyay Deng (Centre for Film and Media Studies, 2022)
In this mini-dissertation, I investigate the manifestation of the political is personal, or rather the structural as personal, by examining what women's experiences within the city of Cape Town reveals about structural, social, and political structures as they relate to safety. This is done through critically reflecting upon both the participatory creation process and conducting a qualitative content analysis of each episode of the web series Thinking Safety that I produced as the creative research component of this masters dissertation. The creation of this series used an interdisciplinary design-based ethnographic research methodology to prompt actionable discussions around the physical manifestations of the lack of structural safety. This paper explores the ways in which this methodology renders women's experiences more perceptible in its exploration of the tangible aspects of how safety and unsafety is experienced. The creative research explores the space between participants' realities and an imagined space of absolute safety and deliberates upon their responses that frame their experiences in relation to social, structural constructs, and spaces. Participants answer specific pre-researched questions that inquire upon safety, spatial navigation, responsibility and design and these responses are creatively compiled in the experimental web-series Thinking Safety which is reflected upon in this paper. This research reveals how the lack of structural safety has led to a distortion of the notion of responsibility as both patriarchal culture and state neglect has exacerbated the unsafety of women in Cape Town. Structural constructs are also viewed as being deliberately created, through the existence of harmful social-cultural norms and this neglect of structural responsibility. Safety mechanisms are then derived from the participant's responses, which deliberate upon imagination, responsibility, visibility, and ethical interdependency as mechanisms for safety creation. This conceptual imagination of safety co-creation is then presented as a purposeful idealisation of democratised and co-developed futures. This paper therefore explores the democratic potential of participatory design-based ethnographic filmmaking, in its expressions of the supressed aspects of our experiences and the potentials for their transformation.